The influence of visual and hearing stimuli on the performance of young tennis athletes aged 12-15 years - Aggelos, Stamboulis; A, Mavvidis; V, Dimitriou; A, Giampanidou (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2016)
The purpose of the study was to examine the effects of visual and hearing influences on the performance of young tennis players aged between 12 15 years old. The sample comprised 60 athletes, 30 males and 30 females respectively with the average age of 13,61 ( + 1,48 ) years and previous competitive experience in local and/or peripheral levels. The method used during the study was completed in two sessions. Firstly, all participants were measured according to two variables (precision, score) while performing a forehand and a backhand drive test where competence was being registered. The measurings during the performance of these two strikes were imitially realized with the insertion of visual and later of hearing stimuli. A week later, the measurings were repeated using the same sample (reliability control). The results proved that the values of the second measuring were clearly better than the values of the first one. However, the measuring`s reliability ranges within satisfactory levels (r=.83). Moreover, the negative effects of visual and hearing influences upon the athlete`s performance proved to be mainly visual and secondly hearing. In conclusion, the present study showed that the visual and hearing influences have negative effects on the performance of young tennis players between 12 15 years of age, who should be trained accordingly, so as to overcome successfully those influences and perform their best!